Transnational Human Resource Management – The More The Better? - Conceptualisation and Case Research in Spain, Britain and Germany - Dickmann, Michael (Cranfield University, 2000)
Some authors have argued that in an increasingly integrated world economy an ideal multinational company (MNC) should be simultaneously locally responsive, globally efficient and innovative world-wide. Bartlett and Ghoshal (1989, 1998) suggest that a ‘transnational’ firm overcomes the global-local dilemma while being a highly innovative organisation and that MNCs should strive to follow this supra-national business logic to acquire competitive advantage. A key step to become such an ideal firm is to implement transnational HRM. This raises the issue of whether MNCs should take up these recommendations. If they do, what outcomes are associated with transnational